Identification and Classification of Downy Mildew Severity Stages in Watermelon Utilizing Aerial and Ground Remote Sensing and Machine Learning - Abdulridha, Jaafar; Ampatzidis, Yiannis; Qureshi, Jawwad; Roberts, Pamela (Frontiers in Plant Science, 2022)
Remote sensing and machine learning (ML) could assist and support growers, stakeholders, and plant pathologists in determining plant diseases resulting from viral, bacterial, and fungal infections. Spectral vegetation indices (VIs) have shown to be useful for an indirect detection of plant diseases. The purpose of this study was to utilize ML models and identify VIs for the detection of downy mildew (DM) disease in watermelon in several disease severity (DS) stages, including low, medium (levels 1&2), high, and very high. Hyperspectral images of leaves were collected in the laboratory by a benchtop system (380 nm-1000 nm) and in the field by an UAV-based imaging system (380 nm-1000 nm). Two classification methods, multilayer perceptron (MLP) and decision tree (DT), were implemented to distinguish between healthy and DM-affected plants. The best classification rates were recorded by the MLP method; however, only 62.3% accuracy was observed at low disease severity. The classification accuracy increased when the disease severity increased (e.g., 86%-90% for the laboratory analysis, and 69%-91% for the field analysis). The best wavelengths to differentiate between the DS stages were selected in the band of 531 nm, and 700 nm to 900 nm. The most significant VIs for DS detection were the chlorophyll green (Cl green), photochemical reflectance index (PRI), normalized phaeophytinization index (NPQI) for laboratory analysis, and the ratio analysis of reflectance spectral chlorophyll-a,b&c (RARSa, RASRb, & RARSc) and the Cl green in the field analysis. Spectral VIs and ML could enhance disease detection and monitoring for precision agriculture applications.